Pengaruh Belanja Modal, Investasi, dan Tenaga Kerja terhadap PDRB Sektor Industri Pengolahan di Provinsi Jambi - Eristian Wibisono; Amri Amir; Zulfanetti Zulfanetti (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2019)
Impact of Capital Expenditure, Investment, and Labour on Gross Regional Domestic Product of Manufacturing Sector in Jambi Province The manufacturing sector contributes significantly to the Gross Regional Domestic Product (GRDP) of Jambi Province. However, despite the realization of regional government capital expenditure, labor, and private sector investment continued to increase, the contribution of this sector showed a negative trend and its growth rate also experienced a slowdown. This study aims to analyze the effect of capital expenditure, investment, and labor on GRDP of the manufacturing sector in Jambi Province. This study uses secondary data of districts and cities in Jambi Province obtained from the Statistics Indonesia (BPS), Regional Investment Board (BPMD), Ministry of Finance of the Republic of Indonesia, and other supporting agencies during 2011–2015. This research begins with descriptive analysis method to analyze the development of the variables observed, then concluded based on quantitative statistical analysis method to analyze the effect of capital expenditure, investment, and labor on the economy of the manufacturing sector. Results of the analysis indicate that capital expenditure, investment, and labor simultaneously and partially have positive and significant effects on the GRDP of the manufacturing industry sector in Jambi Province.